ANALISIS PENYALURAN BANTUAN SOSIAL PADA MASA PEMILU PERSPEKTIF SILA KEADILAN SOSIAL BAGI SELURUH RAKYAT INDONESIA - Sri Hartati; SRI SETIAWATI; Rubiyanto Rubiyanto (UNTAG Law Review, 2025)
The social assistance program (Bansos) has become the main instrument in the government's performance to alleviate poverty and ensure community welfare. However, the phenomenon of misuse of social assistance for political purposes, especially in the context of general election campaigns (Pemilu), is an issue that raises serious concerns in realizing the principles of justice, transparency, and accountability in realizing elections that are "Luber Jurdil" (Direct, Public, Secret, Honest, and Fair). The purpose of this paper is to identify and examine carefully and thoroughly the normative problems related to the misuse of social assistance programs for campaign purposes during the general election. This research uses a normative analysis method by referring to various legal sources, regulations, and related literature. To deal with this issue, this article adress several policy recommendations, including strengthening legislative material regarding supervision and accountability, increasing the capacity of related institutions, as well as increasing awareness of law and political ethics among the public and political actors. So the misuse of social assistance programs for campaign purposes during general elections is a complex problem and requires comprehensive and sustainable action from various related parties to build transparent, clean, and accountable public governance.